An Australian Indigenous common law right to participate in decision-making. (2nd January 2020) - McCabe, Patrick
ABSTRACT: Article 18 of the United Nations Declaration of the Rights of Indigenous Peoples provides that Indigenous peoples have the right to participate in decision-making about matters affecting their interests. This is a right Australian Indigenous people largely do not enjoy. Its absence is felt keenly by First Nations people. The 2017 First Nations National Constitutional Convention Uluru Statement from the Heart is a landmark declaration of Indigenous peoples' desire for recognition in Australia's Constitution. Its principal demand was the creation of a First Nations Voice, a constitutionally enshrined Indigenous representative body which the Australian Government would be required to consult on decisions affecting Indigenous people. This paper considers Canadian jurisprudence and recent developments in Australian native title jurisprudence in order to argue that it is now open for the common law of Australia to develop to recognise a limited Indigenous right to participate in government decision-making about Indigenous matters.